THE RELATIONSHIP BETWEEN ANALYTICAL SKILLS AND THE STAGES OF THE CASE METHOD IN DETERMINING THE BEST SOLUTION - Mihardi, Satria; Derlina, Derlina; Siregar, Alkhafi Maas; Simanjuntak, Yanthy Leonita P. (Universitas Quality, 2023)
The case method reports descriptive information regarding a trial or experiment, event or analysis, or project. The case method can also be interpreted as the result of intensive and systematic investigations carried out by individuals, groups communities, or units to examine data that is related to several variables. Students or teachers usually take a broad and complex topic or phenomenon in the case method. Then, the topic is narrowed down to the questions to be analyzed. Analysis is an activity that consists of a series of activities such as; parsing, distinguishing, and sorting things to be regrouped according to certain criteria and then looking for connections and interpreting their meaning. The ability to analyze is one of the high-level cognitive abilities that is important for students to master in learning. The selection of control and experimental samples was carried out using class random. This is done to reduce bias when determining or drawing conclusions that may result in adjustments to the circumstances being made. The form of research is a quasi-experiment with a two-group pretest-posttest type. Data analysis in this research was carried out descriptively by determining the residual regression test with the help of the SPSS program. The treatment given through the case method makes analysis the basic and most developed ability in learning. These results prove that the case method analysis each stage of students' basic thinking in providing arguments and conclusions based on the thought analysis itself. Analytical skills can be developed through the case method stages. The case method stages require analysis at each stage to provide arguments and possible solutions. Repeated training helps students improve their analytical skills.